2021
DOI: 10.1136/bmjopen-2021-054728
|View full text |Cite
|
Sign up to set email alerts
|

Mental burden and perception of the study situation among undergraduate students during the COVID-19 pandemic: a cross-sectional study and comparison of dental and medical students

Abstract: ObjectivesTo investigate levels of distress, depression, anxiety, stress and perception of their current study situation during the COVID-19 pandemic among undergraduate dental and medical students.DesignObservational, cross-sectional study including two consecutive surveys (May and July 2020).SettingA large medical school in Germany.ParticipantsAll first year dental and medical students were invited. 132 participating first year students (44 dental, 88 medical) from the first survey and 150 students (50 denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
2
28
1
1
Order By: Relevance
“…Medical, dental, and healthcare education are in general regarded as emotionally and academically demanding, and the prevalence of anxiety and depression is higher than in the general population [ 3 , 9 , 10 , 11 ]. According to a meta-analysis of Quek et al, the prevalence of anxiety among medical students was 33.8%, whereas in the general population, did not exceed 25% depending on different surveys [ 10 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medical, dental, and healthcare education are in general regarded as emotionally and academically demanding, and the prevalence of anxiety and depression is higher than in the general population [ 3 , 9 , 10 , 11 ]. According to a meta-analysis of Quek et al, the prevalence of anxiety among medical students was 33.8%, whereas in the general population, did not exceed 25% depending on different surveys [ 10 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis of Quek et al, the prevalence of anxiety among medical students was 33.8%, whereas in the general population, did not exceed 25% depending on different surveys [ 10 , 12 , 13 ]. Moreover, Guse et al showed that dental students were even more distressed than medical students during the pandemic [ 9 ]. Many factors influence this situation, among others the workload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both scales offered the following possible responses: (0) not at all, ( 1 ) several days, ( 2 ) more than half the days, and ( 3 ) nearly every day. The total GAD-7 score was the sum of the coded responses and its ranges indicated: no anxiety symptoms (0–4), mild anxiety symptoms ( 5 9 ), moderate anxiety symptoms ( 10 14 ), and severe anxiety symptoms (15 and more). The severity ranges of the total PHQ-9 score were as follows: no depressive symptoms (0–4), mild depressive symptoms ( 5 9 ), moderate depressive symptoms ( 10 14 ), moderately severe depressive symptoms ( 15 19 ), and severe depressive symptoms (20 and more).…”
Section: Methodsmentioning
confidence: 99%